1995
DOI: 10.1103/physrevd.52.4718
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical flavor symmetry breaking by a magnetic field in 2+1 dimensions

Abstract: It is shown that in 2 + 1 dimensions, a constant magnetic field is a strong catalyst of dynamical flavor symmetry breaking, leading to generating a fermion dynamical mass even at the weakest attractive interaction between fermions. The essence of this effect is that in a magnetic field, in 2 + 1 dimensions, the dynamics of fermion pairing is essentially onedimensional. The effect is illustrated in the Nambu-Jona-Lasinio model in a magnetic field.The low-energy effective action in this model is derived and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
270
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(287 citation statements)
references
References 53 publications
17
270
0
Order By: Relevance
“…It has been shown that a constant magnetic field acts as a strong catalyst of dynamical chiral symmetry breaking, thus leading to the generation of a fermion mass [1,2]. The physics behind this effect is easy to understand: the motion of a charged particle is restricted to directions perpendicular to the magnetic field and this leads to a dimensional reduction (d → d − 2) in the dynamics of the fermion pairing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that a constant magnetic field acts as a strong catalyst of dynamical chiral symmetry breaking, thus leading to the generation of a fermion mass [1,2]. The physics behind this effect is easy to understand: the motion of a charged particle is restricted to directions perpendicular to the magnetic field and this leads to a dimensional reduction (d → d − 2) in the dynamics of the fermion pairing.…”
Section: Introductionmentioning
confidence: 99%
“…Section 4 is devoted to test our formalism against the well-known results of the local Nambu-JonaLasinio (NJL) model [7], setting the stage for the new results concerning nonlocal kernels in the presence of magnetic fields. In particular, we show how to translate the formulae and results obtained within the present formalism to the ones usually obtained through the use of mean-field techniques [1,2]. This translation is a validation of our formalism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most interesting topics in the studies of (2+1)-dimensional theories is the parity and chiral symmetry-breaking. In particular, it has been shown that a background magnetic field can serve as a catalyst for the dynamical symmetry breaking [7,8]. In addition, the background gauge fields give rise to the polarization of the ground state for quantum fields with the generation of various types of quantum numbers [4,9].…”
Section: Introductionmentioning
confidence: 99%